Acute Toxicity of Tomato Extract (Lycopersicum esculentum) on Rat’ Liver - Iswari, Retno Sri; Yuniastuti, Ari; Widiatningrum, Talitha (KnE Social Sciences, 2019)
Tomato extract (Lycopersicum esculentum) is commonly used as traditional medicine because of its antioxidant activity. As a traditional medicine, tomato extract uses for therapy. Therefore, it is important to note that the safety aspect does not cause toxic effects. This study aimed to determine the acute toxicity of tomato (Lycopersicum esculentum) extract on the liver of Sprague Dawley rats (SD) by looking at the activity of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alacaline phosphatase (ALP), gamma glutamyl transpeptidase (GTP) and features liver organ histopathology. Acute toxicity test was carried out by giving tomato extract orally in doses of 16, 160, 1600 and 16000 mg/ individual. Toxicity observations were carried out within 14 days after administration. The activities of AST, ALT, ALP and GGT were analyzed using Diasys kit for research purpose. The results showed that the activity of AST, ALT, ALP and GGT was not signiﬁcantly different in the treatment group with the control group (p<0.05) and histopathology found some changes in cell structure and tissue in the liver organ but this change did not indicate the occurrence of toxic damage. The conclusion of this study is that no acute toxic effects were found from tomato extract (Lycopersicum esculentum) on SD rats. Keywords: acute toxicity, tomato extract, liver histopathology